Bilateral internal thoracic artery use in coronary artery bypass grafting in the post-ART era - Perspective. (February 2021) - Sef, Davorin; Raja, Shahzad G.
Abstract: There is still lack of convincing evidence about the superiority of bilateral internal thoracic artery (BITA) use in coronary artery bypass grafting (CABG) and BITA grafts continue to be underutilized. Arterial Revascularization Trial (ART) did not demonstrate the superiority of BITA versus single ITA grafting after 10 years. We have reviewed the most recent literature, assessed the current status as well as indications of BITA grafting in the post-ART era. We believe that BITA grafting is not appropriate for all patients especially in light of the findings of ART. However, the use of BITA is justified in patients of younger age and those without comorbidities (poorly controlled diabetes, obesity, chronic obstructive pulmonary disease, previous mediastinal irradiation, long-term steroid use, elderly women). Further prospective randomized studies with long-term follow-up are needed to validate the benefits of BITA grafting. Highlights: There is still lack of convincing evidence about the superiority of bilateral internal thoracic artery (BITA) use in CABG surgery. Arterial Revascularization Trial (ART) did not demonstrate the superiority of BITA versus single ITA grafting. Selective approach in choosing patients for BITA could decrease the risk of DSWI while offering potential survival benefit.